2020
DOI: 10.1103/physrevb.101.094404
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous and topological Hall effects in epitaxial thin films of the noncollinear antiferromagnet Mn3Sn

Abstract: Noncollinear antiferromagnets with a D019 (space group = 194, P63/mmc) hexagonal structure have garnered much attention for their potential applications in topological spintronics. Here, we report the deposition of continuous epitaxial thin films of such a material, Mn3Sn, and characterize their crystal structure using a combination of x-ray diffraction and transmission electron microscopy. Growth of Mn3Sn films with both (0001) c-axis orientation and (404 ̅ 3) texture is achieved. In the latter case, the thin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…[ 17,34,37 ] Moreover, the room‐temperature TR‐odd responses remain useful in the same concentration range while the non‐stoichiometry of Mn 3 Sn shifts the Fermi energy by changing the number of conduction electrons. [ 17,21,29,38 ] While the ITS structure is coplanar, recent studies have found that the topological Hall effect may also arise from the non‐coplanar spin structure stabilized in the magnetic domain wall [ 39,40 ] or in the low‐temperature cluster glass phase. [ 17,40 ]…”
Section: Large Tr‐odd Transverse Electrical Responses In Mn3snmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17,34,37 ] Moreover, the room‐temperature TR‐odd responses remain useful in the same concentration range while the non‐stoichiometry of Mn 3 Sn shifts the Fermi energy by changing the number of conduction electrons. [ 17,21,29,38 ] While the ITS structure is coplanar, recent studies have found that the topological Hall effect may also arise from the non‐coplanar spin structure stabilized in the magnetic domain wall [ 39,40 ] or in the low‐temperature cluster glass phase. [ 17,40 ]…”
Section: Large Tr‐odd Transverse Electrical Responses In Mn3snmentioning
confidence: 99%
“…[ 17,21,29,38 ] While the ITS structure is coplanar, recent studies have found that the topological Hall effect may also arise from the non‐coplanar spin structure stabilized in the magnetic domain wall [ 39,40 ] or in the low‐temperature cluster glass phase. [ 17,40 ]…”
Section: Large Tr‐odd Transverse Electrical Responses In Mn3snmentioning
confidence: 99%
“…They are characterized by a lack of inversion symmetry or broken time-reversal symmetry, resulting in two-fold degenerate band-touching points (Weyl nodes) with opposite chirality formed in momentum space [ 3 , 5 , 10 , 11 , 12 ]. The Weyl nodes act as quantized sources and sinks of Berry curvature, which in turn lead to intriguing transport properties, such as the anomalous Hall effect [ 13 , 14 , 15 , 16 , 17 , 18 ], the anomalous Nernst effect [ 19 , 20 , 21 , 22 ], magneto-optical responses [ 23 ] and the chiral anomaly [ 24 , 25 ]. Recently, some ferromagnetic compounds were proposed to be time reversal symmetry breaking Weyl semimetals (WSMs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the thin film fabrication processes have led to the realization of various spintronic devices using the Mn 3 Sn film. [ 26–34 ] In the antiferromagnetic memory made of the Mn 3 Sn/heavy metal multilayers, the electrical current may switch the direction of the ferroic order of the magnetic octupole (Figure 1b). Thus, the information is stored as the polarity of AHE, which may be read out through the sign and magnitude of the anomalous Hall voltage.…”
Section: Introductionmentioning
confidence: 99%